Teaching English language learners in secondary subject matter classes - Dong, Yu Ren (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
"This book is for secondary subject matter teachers and administrators who work with English language learners (ELLs) in subject matter classes. It is also for college professors who prepare pre-service teachers to work with those students. The book brings together insights from linguistic, socio-cultural, educational, cognitive, developmental perspectives of what it means for ELLs to learn both English and subject matter knowledge in English as a second language. It delineates unique challenges that ELLs experience, offers ELLs' learning stories, and suggests concrete strategies with classroom teaching examples across academic disciplines. The 2nd edition broadens the scope of the 1st edition in several aspects. Specifically, it includes two chapters about secondary ELLs' previous educational experiences in their home countries, a chapter on subject matter lesson planning with ELLs in mind with teacher collaborative strategies, and more principle-based and field-tested effective instructional and assessment strategies for working with ELLs"-- Provided by publisher.
Keywords: English language -- Study and teaching (Secondary) -- Foreign speakers.; Second language acquisition -- Study and teaching -- Foreign speakers.; Interdisciplinary approach in education.; Education -- Teaching -- Subjects -- General.; Education of bilingual or multilingual students.; Teaching of a specific subject.; elektronické knihy; electronic books